How does blood-flow restriction alter forehand drive performance and muscle recruitment in tennis players - Han, Z.; Guo, Z.; Yan, B.; Girard, O. (International Journal of Sports Physiology and Performance, 2025)
Purpose To examine the acute effects of forehand drive (FD) preconditioning with or without blood-flow restriction (BFR) on subsequent forehand performance and muscle recruitment in tennis.